Analysis Of Load Variations On ST 60 Steel Using Vickers Method - Hidayat, Hidayat; Jufriyanto, Moh.; Ningtyas, Alviani Hesthi Permata; Yusron, Rifky (Universitas Trunojoyo Madura, 2020)
The use of metal in the industrial world, especially ST60 Steel, is a very vital need, this can be seen from the increasing number of machine or equipment components or construction parts made of steel. Hardness is one of the mechanical properties that is often used as a guide in selecting materials for an equipment component. To find out the hardness price of a material, various testing methods can be used, including the Vickers method, which is tested by applying a force to the indented diamond pyramid against the material for which the hardness value is determined. The amount of hardness value is determined by the magnitude of the loading force divided by the area of indentation. In this study, what was investigated was the effect of force on the hardness of the Vickers method. The results showed that the load variation had little effect on the results of the Vickers hardness value, especially for high loads (100 Kgf). The average hardness value for the mild steel being tested is 163 HV and 168 HV, the highest hardness value is 174 HV and the lowest hardness value is 156 HV, so that a tolerance of ± 10 HV commonly used in the Vickers test is sufficient.Keywords: Hardness, ST 60 Steel , Loading Variations, Vickers Test